Radiation therapists' perceptions of participating in Professional Supervision – a pilot study - Gay Dungey; Sarah Thomson; Paula Rodriguez Lopez (Journal of Medical Radiation Sciences)
Abstract Introduction Professional Supervision (PS) is a common approach used to reduce the fallout from stress and burnout. It involves monthly face‐to‐face meetings between a supervisor and supervisee to address well‐being and professional goals. This pilot study examines 12 radiation therapists (RTs) perceptions of participating in PS. Methods Conducted in the Christchurch Radiation Oncology Centre, this mixed‐methods pilot study introduced PS in March 2022. In August 2023, 12 RTs completed a QUALTRICS online questionnaire consisting of 33 questions, including the Supervisor Working Alliance Inventory (SWAI). The SWAI assessed the alliance of supervision from a supervisee's perspective and comprised of 19 questions on a 7‐point Likert scale and nine yes/no statements with optional comments. Five demographic questions were also included. Results All 12 RTs completed the questionnaire, with quantitative results indicating a positive alliance between supervisors and supervisees. RTs found PS to be a safe and comfortable space for reflective practice and support. Thematic analysis of qualitative data from additional comments revealed PS enabled RTs to reflect on career achievements, appreciate highlights of being an RT and consider future career paths within the profession. Conclusions Radiation therapists responded positively to PS, suggesting its potential in managing workplace stressors, promoting career advancement and providing dedicated time for reflection, support and guidance. RTs endorsed the efficacy of PS in enhancing their practice and advocated for its widespread adoption among RTs.